DETERMINATION OF BIOGENIC AMINES BY USING AMPEROMETRIC BIOSENSORS BASED ON GRASS PEA AMINE OXIDASE AND OAT POLYAMINE OXIDASE - AQUILANTE, Laura; NISTOR, Mihaela; TAORMINA, Stefania; ŠEBELA, Marek; FRÉBORT, Ivo; POPESCU, Ionel Cătălin (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Grass pea amine oxidase (GPAO) and oat polyamine oxidase (OPAO) were immobilized along with horseradish peroxidase (HRP) and an Os-redox polymer (Os-RP) onto the surface of a graphite electrode by cross-linking with poly(ethylenglycol) diglycidyl ether. The resulted reagentless amperometric biosensors were inserted in a flow injection setup and used as electrochemical detectors for the biogenic amines (BA) detection. Both biosensors were operated at low applied potential (-50 mV vs. Ag/AgCl, KCl0.1M) where electrochemical interferences are minimal. The quantification of ten BA (tyramine, putrescine, cadaverine, histamine, cystamine, phenylethylamine, agmatine, tryptamine, spermine, and spermidine) either individual or in mixture (after a preliminary separation by using cation exchange chromatography) was reported. G/(Os-RP)-HRP-GPAO biosensor detected all ten BA, while G/(Os-RP)-HRP-OPAO biosensor detected only spermine and spermidine. Finally, a simple and low-cost method for free and acetylated polyamines determination in human urine samples, by using the highly selective G/(Os-RP)-HRP-OPAO biosensor, was proposed.